British fascism, 1918-1939 : parties, ideology and culture - Linehan, Thomas P. (Manchester : Manchester University Press, 2021)
A major new and balanced study of British Fascism which surveys the development of British fascism between 1918 and 1939. Provides an accessible guide to the essential features of British fascism in the interwar period. Considers a previously under-researched area of British fascism, namely fascism and culture. Explores the various definitions of fascism, before moving on to analyse the origins of British fascism, the fascist parties and groups, fascism and culture, the membership, and British fascist antisemitism.
Previously issued in print: 2000.
Preface and acknowledgementsList of abbreviationsIntroduction: the historiography of fascist studies1. Origins and progenitors2. The early postwar context and the pre-fascist groups: incipient fascism?3. The arrival of fascism: the British Fascisti and the Imperial Fascist League4. The British Union of Fascists5. The minor parties, 'one-man bands' and some fellow travellers6. The membership7. British fascism and antisemitism8. Defining culture9. A host of 'decadent' phenomena10. The city, the countryside and the machine11. Responding to the visual arts: British fascism and artistic modernismBibliography.
Description based on CIP data; resource not viewed.
JSTOR
Keywords: Fascism -- Great Britain; Great Britain -- Politics and government -- 20th century; Fascisme -- Grande-Bretagne.; Grande-Bretagne -- Politique et gouvernement -- 20e siècle.; HISTORY / Europe / Great Britain; Fascism; Politics and government; Great Britain; 1900-1999